Development & characteristic of starch protein based edible film incorporated with tumeric essential oil / Muhammad Luqman Hakim Ahmad Tarmezie - Ahmad Tarmezie, Muhammad Luqman Hakim (2017)
The scope of this research is to synthesize and characterize a starch-protein based film incorporated with turmeric essential oil. The film was synthesized using adopted method from journals. The sample produced was characterized by it mechanical properties and solubility properties. These analyze was conducted using Universal Testing Machine for mechanical properties and weight analyzer for film solubility. Different temperature setup during gelatinization process and different turmeric oil concentration were set as manipulated variables for this experiment. The result was tabulated in result and discussion section, based on previous journal the mechanical properties will increase when temperature and concentration of turmeric oil, same trend can be seen for solubility properties. However some studys show the totally opposite result, hence study has been coducted and compared with previous result.